If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x=52x+13=
We move all terms to the left:
x-(52x+13)=0
We get rid of parentheses
x-52x-13=0
We add all the numbers together, and all the variables
-51x-13=0
We move all terms containing x to the left, all other terms to the right
-51x=13
x=13/-51
x=-13/51
| 5x-6x=35 | | x+10=9+3 | | (3.45x10^=(3))+(6.11x10^(3)) | | -11+x=35 | | 8v+6=14 | | 3.5=7.1-0.9x | | x+(-6)=34 | | r/2+4=15 | | 3(4y+5)=-21 | | 2/3×c=5/8 | | n-3/4=1/4 | | 5(41)-43=80+z | | 90+(4x+18)+(3x+9)=180 | | 171+2h=1007 | | 0.15(x+1,000)=6,450 | | 3=x+23/6 | | 3x-5=+23x-9 | | 4c-7=24 | | 15=2.5m | | 1/2(n+3)=10 | | 0.35x+2=0.25+5 | | 2(u+5)=14 | | 2s+9=19 | | 4f+23=-7 | | 90+(2x+31)+(4x-7)=180 | | 5s+19=19 | | 23=2w+7 | | (1^x^2)(1^x)=1^20 | | 6x−28=−76 | | 11,402.7-b=1889.1 | | 8m=$3600 | | 8m=$36 |